Potential Impact of Nuclear Power on Water Resources in the Southeast United States - Matthew Herald (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2016)
Water stress threatens to impact electricity production from thermoelectric plants in the Southeast United States (SE). This is concerning because 97.4% of electricity in the region is produced from thermoelectric sources. These coal, nuclear, and natural gas plants require water for waste heat rejection (WHR), comprising the majority of the SE’s water consumption (58.9%). Increasing nuclear power has been proposed as a way to reduce carbon emissions while being an efficient utilization of land resources compared to wind or solar. However, the impact of an increased reliance on water resources should be examined. To do this, it is necessary to characterize the SE’s electricity mix, water utilization, and determine how these resources are used. In 2010, nuclear plants produced 22.5% of the electricity in the SE, yet comprised 36.8% of the thermoelectric water withdrawal. Thermoelectric plants withdrew the majority of water in the region (58.9%). Only a fraction of withdrawals are consumed by evaporation, but warmer water is returned to streams, which can have harmful effects on aquatic ecosystems. Nuclear plants have larger water withdrawals per GWh because of their lower thermal efficiencies. As more nuclear plants are added to the region, the thermoelectric water demand will grow. To reduce the amount of water needed for WHR, it is advantageous to build cooling towers in waterstressed areas because of their low water withdrawals and to slowly phase out once-through WHR except in areas where environmental impact is negligible. Technologies that could better utilize water resources such as dry heat rejection, waste heat recovery for desalination, and high-temperature reactors with higher thermal efficiencies, like salt-cooled reactors and supercritical CO2 systems, should be considered.